Not Just for Dancing? A Content Analysis of Concussion and Head Injury Videos on TikTok - Carter, Peyton N.; Hall, Eric E.; Ketcham, Caroline J.; Ahmed, Osman H. (Frontiers in Sports and Active Living, 2021)
Social media platforms are an accessible and increasingly used way for the public to gather healthcare-related information, including on sports injuries. “TikTok” is currently one of the fastest-growing social media platforms worldwide, and it is especially popular amongst adolescents and young adults. The widespread use and popularity of TikTok suggests that this platform has potential to be a source for healthcare information for younger individuals. This exploratory study used a systematic search strategy to understand more about how concussion is being portrayed through TikTok videos. Using the keywords “concussion” and “head injury”, 200 videos were downloaded from TikTok and 43 videos were excluded. Of the 92 videos retrieved using the keyword “concussion”, 95% (n= 88) had more than 100,000 views and 6% (n=10) had been viewed more than 10 million times. Over half, 54% (n=50) of the “concussion” videos depicted individuals “playing around” and getting hit in the head, whilst only 1% (n=1) of the TikTok videos were categorised as “explaining concussion facts”. The large numbers of views of concussion-related TikTok videos demonstrates the popularity of this platform and indicates that healthcare organizations should consider TikTok as a potential means for concussion education amongst younger individuals.